3D printing services: classification, supply chain implications and research agenda - Rogers, Helen; Baricz, Norbert; Pawar, Kulwant S. (Emerald, 2016)
Purpose: The purpose of this paper is to identify and classify the available types of 3D printing services, with the scope of determining the potential implications that such services could have on the supply chains of manufacturing firms and creating a research agenda for future studies. Design/methodology/approach: The authors review the current literature on the potential supply chain impacts of 3D printing and evaluate the 3D printing services provided by 404 firms in selected European markets. Findings: The results show that 3D printing services form a rapidly evolving industry, with new service providers entering the market on a regular basis. Evidence from the European markets investigated suggests that services can be classified into three distinct categories: generative, facilitative and selective services. Research limitations/implications: This paper represents an attempt to take stock of a fastmoving and potentially paradigm-shifting market. The implications are dynamic as new applications, business models and techniques are continually being developed. Further studies are required to substantiate the findings. Practical implications: Three categories of 3D printing services that could significantly impact supply chain configurations of the future are proposed. Several issues specific to 3D printing services raised in the research agenda require further scrutiny and substantiation before services can reach their full potential. Originality/value: This paper provides an overview of the growing 3D printing services industry, highlighting how the market might change as additive manufacturing technology matures.